Levels, Trends and Differentials of Teenage Childbearing in India - Pautunthang, N. (Asian Journal of Population Sciences, 2023)
Teenage childbearing occurs in every society worldwide. Teenagers are understudied and a complex age group to reach. It is essential to know the levels and trends of teenage childbearing with its socio-economic and demographic differentials. Therefore, the overall purpose of the present study is to explore the levels, trends, and differentials of teenage childbearing in India. The required data were obtained from National Family Health Survey (NFHS). The analysis is based on the samples of 24,811 women aged 15-19 in 2005-06 (NFHS-3), 1,21,552 in 2015-16 (NFHS-4) and 1,22,544 in 2019-20 (NFHS-5). Descriptive statistics and binary logistic regression analysis have been carried out by using SPSS-23. In NFHS-5, the proportion of teenage childbearing is 6.8 per cent, which showed a decline from 16.0 per cent in NFHS-3. Tripura (21.9%) has the highest teenage childbearing percentage, whereas Ladakh had zero teenage childbearing. Among the districts in India, Dhalai district (28.2%) in Tripura has the highest percentage of teenage childbearing. The percentage of teenage childbearing is significantly higher in rural areas than in urban areas, except in Goa and Himachal Pradesh. Higher educational attainment and a rich household wealth index are associated with a lower incidence of teenage childbearing. Except for the NFHS-3, teenage childbearing is comparatively higher among Muslims than among other religions. Exposure to media helps in reducing teenage childbearing. Teenage childbearing is higher among the Scheduled Tribe (S.T) than in other castes. Despite some progress, more has to be done to minimise teenage childbearing in India.